Pendugaan Fungsi Penawaran Normatif untuk Komoditas Palawija Berdasarkan Pemanfaatan Pola Tanam Optimal pada Lahan Kering di Lombok - Fachrur Rozi (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1993)
The aim of the research is to reveal the opportunity of increasing regional production in Lombok Island by optimal utilization of dry land, as commodities supply alternative of palawija. The survey was done in dryland area in Lombok, during May-August 1992. The analysis was conducted using linier programming. The results showed that design of optimal cropping patterns were able to increase region's production and income. Moreover, by knowing normative supply of the product, supply of the commodities can be manipulated by using the optimal cropping patterns.